Manual for Preclinical Removable Prosthodontics: Complete Dentures - Marjan Moghadam; Bijan Moghadam; Leila Jahangiri (Association of American Medical Colleges, 2009)
Abstract The Manual for Preclinical Removable Prosthodontics includes step-by-step instructions with color photographs of procedures involved in making complete dentures. This manual is the main information guide for the preclinical laboratory sessions at the New York University College of Dentistry. It is also being utilized as a review on the treatment of patients by clinic students, as well as for standardization of faculty. The manual is currently being used in the preclinical simulation lab sessions for training of predoctoral students at the institution.